1999
DOI: 10.1111/j.1469-7793.1999.00351.x
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive β2‐adrenergic signalling enhances sarcoplasmic reticulum Ca2+ cycling to augment contraction in mouse heart

Abstract: Excitation-Ca¥ release coupling is a pivotal event in cardiac function. During membrane depolarization, sarcolemmal Ca¥ influx through the voltage-operated L_type Ca¥ channels triggers the sarcoplasmic reticulum (SR) to release Ca¥ via the Ca¥-induced Ca¥ release (CICR) mechanism (Fabiato, 1983). The resultant cytosolic Ca¥ transient activates myofilament proteins and initiates contraction. Cardiac relaxation ensues when the elevated cytoplasmic Ca¥ is resequestered by the SR Ca¥ pump, or, to a lesser extent, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 57 publications
5
68
0
1
Order By: Relevance
“…The distributions of these characteristics were asymmetrical due to detection limits of the smaller Ca 2ϩ sparks. Broad modal distribution of Ca 2ϩ spark amplitudes has been described earlier (8,12,17,29,35) and differs from the monotonic decaying distribution theoretically predicted (5), probably because the present method restricted the "out-of-focus" events. Ca 2ϩ spark distribution has been previously adjusted to a simple (20), bimodal (31), or multicomponent (30) Gauss function.…”
Section: Methodsmentioning
confidence: 67%
“…The distributions of these characteristics were asymmetrical due to detection limits of the smaller Ca 2ϩ sparks. Broad modal distribution of Ca 2ϩ spark amplitudes has been described earlier (8,12,17,29,35) and differs from the monotonic decaying distribution theoretically predicted (5), probably because the present method restricted the "out-of-focus" events. Ca 2ϩ spark distribution has been previously adjusted to a simple (20), bimodal (31), or multicomponent (30) Gauss function.…”
Section: Methodsmentioning
confidence: 67%
“…Despite this concern, transactivator lines have been developed that show no cardiotoxicity for at least 6 months, and so these experimental limitations can be easily circumvented [250]. cycling of the SR, which showed decreased PLN expression [242,326] Other studies showed that mice die earlier from severe HF indicated by cardiac dilation, pulmonary congestion and pleural effusion [58,159] In CHF, there is selective down-regulation of b1-AR and desensitization of both b1-AR and b2-AR (mediated by b-ARK1)…”
Section: General Considerationsmentioning
confidence: 99%
“…32 Both of ␤ 1 AR and ␤ 2 AR stimulate the classic G s -adenylyl cyclase-3Ј,5Ј-adenosine monophosphate (cAMP) protein kinase A (PKA) signaling cascade. 33 Therefore, activation of ␤-adrenergic receptors may also involve a cAMP-independent mechanism in the regulation of Cx expression.…”
Section: Ade4mentioning
confidence: 99%